Exploring Local Wisdom: The Role of Ethnography in Public Policy Research, A Narrative Review - Puspitasari, Tri Fitriani; Nanang Suko Sadono; Muhammad Royhan; Suhartanto (Jurnal Kebijakan Pembangunan, 2025)
Ethnography, as a qualitative research method, plays a crucial role in understanding the social and cultural dynamics of a community. This study aims to explore how ethnography can uncover local wisdom and provide valuable insights into the development of public policy. By employing an ethnographic approach, researchers become directly involved in the everyday lives of the community, allowing them to capture the meanings and values underlying social actions. Through a narrative literature review analysis, this article provides depth, demonstrating that a deep understanding of the local context not only contributes to the validity of proposed policies but also strengthens community engagement in governance processes. Thus, ethnography serves as a bridge between theory and practice, ensuring that public policies developed are more responsive to the needs and aspirations of the communities they serve.